The Making of Articulate Storyline-Based Learning Multimedia on the Topic of Heat & Temperature - Luh Sukariasih; Muhammad Anas; Diah Putri Rahayu; La Tahang; Suritno Fayanto (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study aims to develop learning multimedia and assess the feasibility level of multimedia as a learning medium used in the learning process. Multimedia is developed using articulate storyline software that can be accessed using smartphones and other devices such as computers. This research and development research was created using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The initial stage is conducting an initial analysis and then making an initial design like storyboards and flowcharts. The multimedia that has been designed is validated by experts and then implemented. Implementation is carried out with limited trials on 15 Class VII students of SMP Negeri 1 Meluhu. Data collection techniques used in this study were interview, checklist, and test techniques. The instruments used are in the form of a multimedia validation sheet that is used to assess the validity of multimedia, student and teacher response questionnaire sheets that are used to evaluate the practicality of multimedia, as well as learning outcomes tests that are used to determine the increase in student learning outcomes after using multimedia. The results showed: (1) the multimedia validity obtained from multimedia experts' validation results using the Aiken index (V). The average value of the validation results was 0.78; (2) the effectiveness of multimedia obtained from the effects of increasing student learning using the n-gain test was 0.56, and the percentage value of effectiveness was 66.67%; (3) the practicality of multimedia obtained from the results of teacher and student responses, where the results of the teacher response assessment got the percentage of the practicality of 90% and the percentage of the practicality of student responses obtained by 86.56%.